Gerakan Masyarakat Hidup Sehat (Germas) di Kelurahan Legok Kota Jambi - Hidayat, Muhammad; Arifarahmi, Arifarahmi; Pranata, Heri; Astuti, Desi (3031-8572, 2023)
Changes in the lifestyle of an increasingly modern society is one of the foundationsHealthy Living Community Movement (GERMAS) was launched by the Ministry of Health of the Republic of Indonesia. The concept of health behavior is defined as a person's response to stimuli associated with illness, disease, the health care system, food, drink, and the environment. The partner problem is the amount of waste that has not been managed properly. This community service method was carried out in March-July 2021 at RT 11, Legok Village, Danau Sipin District, Jambi City through surveys, observations, interviews, lectures, question and answer meetings in 12 meetings, attended by 10 residents. The material provided is different at each counseling session. As a result of this community service, the family works together and disposes of garbage according to the type and place of disposal as wellthere isenvironmental hygiene behavior change.In conclusion from the results of simple measurements the level of knowledge of the pretest and posttest participants increased. Most families understand how environmental hygiene behavior changes. there is an increase in knowledge in accordance with the objectives of community service activities.